Analysis of the nutritional status of adults with hypertension in the capital cities of northeast Brazil, 2013 to 2023: Ecological study (Revista Contexto & Saúde, 2026)
Systemic arterial hypertension, known as high blood pressure, could affect 60% of the world's population by 2025, with approximately 7.1 million deaths annually. The national prevalence of excess weight has increased over the years and acts as a risk factor for complications of the disease. Monitoring the nutritional status of hypertensive patients helps to set goals and promote actions to improve health and prevent diseases. The objective of this study was to analyze the nutritional status of hypertensive adults in the capitals of the Northeast from 2013 to 2023. This is an ecological study using secondary data from Vigitel in the capitals of the Northeast from 2013 to 2023, including adults with hypertension aged 18 to 59 years. Sociodemographic characteristics and nutritional status were assessed using BMI. The findings of this study showed a decrease in hypertensive adults in 2014 and 2023, as well as a high prevalence of overweight, mainly in males, with higher education/postgraduate education, aged 40 to 49 years, and in the capital Natal. It was concluded that there was a high prevalence of overweight in hypertensive adults, which affects health costs and may hinder primary care in prevention policies, as well as socioeconomic disparities in the Northeast region, enabling the targeting of resources in these more vulnerable areas.